Improbable frequency? Advocating queer–feminist pedagogic alliances within Irish and European higher education contexts. Issue 1 (February 2017) - Quilty, Aideen
Heterosexist ideology underpins education policy and practice almost universally. It has the effect of rendering invisible and disrespecting practitioners and students of other sexual and non-gender conforming identities. Much explicitly queer work has challenged this normalising and frequently oppressive higher education terrain. To maximise this queer potential this article proposes re-positioning queer within and through a practice and pedagogy of feminism. The broad-based identity politics of feminism and the anti-identitarian politic of queer may appear a slightly improbable alliance. The article argues, however, that intersectional approaches which reinforce queer integrity, challenge oppressive social norms and simultaneously re-emphasise the importance of the political through an identity politics heavily influenced by feminism, are not just possible but necessary. In seeking to explore what unites feminism and queer educationally, the article makes three observations relating to history, pedagogy and activism. It references two particular LGTBQ Irish and European educational programmes, which it argues highlight this sense of the probable in terms of queer–feminist educational alliances. Such alliances can continue to challenge in material ways sustained educational constructions of heterosexuality as normal, natural and moral and in so doing provide a platform for empowerment and change.